The Dynamics of Gender Power Relations in Families of Indonesian Female Migrant Workers: A Study of Seesaw Marriage - Esa Septian; Septi Wulandari; Mahmoud Ali Mussa (Legitima : Jurnal Hukum Keluarga Islam, 2026)
Purpose – This study aims to analyze how the migration of Indonesian female migrant workers reshapes gender power relations within the family and to propose Hanna Rosin’s concept of seesaw marriage as an adaptive model for sharing breadwinning and caregiving roles. Methods – This study employed a Systematic Literature Review (SLR) following the PRISMA 2020 guidelines. The literature search was conducted using the Scopus database. Of the 356 articles initially identified, 14 articles published met the inclusion criteria and were analyzed thematically. Findings – The findings indicate that women’s migration abroad increases their control over remittances, strengthens their bargaining position, and expands their involvement in household decision-making. These changes encourage a shift in family structure from hierarchical patriarchal arrangements to more negotiated and egalitarian relationships. However, this transformation also generates various tensions, including threats to husbands’ masculine identity, conflicts over financial management, reduced emotional intimacy in long-distance marriages, higher rates of divorce, and psychosocial problems among left-behind children. The concept of seesaw marriage offers an adaptive framework that enables husbands and wives to alternate productive and reproductive roles according to family needs. Research implications – Theoretically, this study enriches the literature on gender and migration by integrating theories of household power relations with the concept of seesaw marriage, demonstrating that family authority is increasingly shaped by economic contributions and the capacity to negotiate roles. Practically, the findings underscore the importance of family resilience-based migration policies, including marital counseling, financial literacy, child caregiving support, and gender equality education. Originality/value – This study offers a novel integration of gender power relations, Indonesian female migrant workers, and the concept of seesaw marriage as an analytical framework for understanding transnational families.